Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557034
|View full text |Cite
|
Sign up to set email alerts
|

The department of hidden stories

Abstract: We detail the design of the Department of Hidden Stories (DoHS), a mobile-based game to support playful digital storytelling among primary school children in public libraries. Through a process of iterative design in collaboration with library staff and children's writers we designed DoHS to support the potential for playful storytelling through interactions with books. A deployment of DoHS with two classes of 8 to 10 years olds as part of their regular library visits revealed insights related to how to balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…While previous work has explored the value of playful engagement in civic spaces such as libraries [68], our study also demonstrated the value of digitally supported roleplay and walks as mediums for children to explore urban issues and participate in transforming their localities. The children were assigned specific responsibilities in their groups, in order to match their preferences and abilities, but also to foster collaboration within the groups.…”
Section: Engaging Children In Political Processes Through Hcimentioning
confidence: 63%
See 1 more Smart Citation
“…While previous work has explored the value of playful engagement in civic spaces such as libraries [68], our study also demonstrated the value of digitally supported roleplay and walks as mediums for children to explore urban issues and participate in transforming their localities. The children were assigned specific responsibilities in their groups, in order to match their preferences and abilities, but also to foster collaboration within the groups.…”
Section: Engaging Children In Political Processes Through Hcimentioning
confidence: 63%
“…Previous work has also investigated how HCI might be able to support children's engagement in civic life [67,68]; however, there remains a need for this work in specific relation to engagement with civic processes such as placemaking. Allied with this, HCI is increasingly recognising the need to 'dig where they stand' and recognise children as "capable social actors" [26:224].…”
Section: Designing Socio-technical Engagementmentioning
confidence: 99%
“…Cao et al's TellTable [2010] supported sketch-based storytelling on an interactive table, aiming to encourage incorporating physical objects into stories via 'capture tools' that inserted photos directly on to the story surface. Other approaches have included those of Jacoby and Buechley [2013], who used conductive ink to allow sketches to be augmented with digital content; de Lima et al [2014], who used pen and paper sketches to insert characters into a virtual world; or, Wood et al [2014], whose barcode scanning approach linked digital tales to physical books. Yeh et al's approach [2006] aimed to produce a merged digital version of both Anoto-marked paper notebooks and related photos.…”
Section: Annotation As Storytellingmentioning
confidence: 99%
“…Other approaches have included those of Jacoby and Buechley [11], who used conductive ink to allow sketches to be augmented with digital content; de Lima et al [15], who used pen and paper sketches to insert characters into a virtual world; or, Wood et al [33], whose barcode scanning approach linked digital tales to physical books. Yeh et al's approach [34] aimed to produce a merged digital version of both Anoto-marked paper notebooks and related photos.…”
Section: Annotation As Storytellingmentioning
confidence: 99%